Emotional Competencies and Responsible Decision Making in Pre-Adolescents with the Support from Teachers, Fathers, and Mothers: A Comparative Study in 4th to 6th-Grade Students of Primary Education in Spain - Márquez-Cervantes, Ma. Concepción (2018)
This article aims to analyze the relationship between emotional competencies and responsible decision making in pre-adolescents, and the support of teachers and parents in this process, which could help students to solve problems and face risk situations in a better way. A quantitative, descriptive correlation and cross-sectional type research was carried out to achieve this aim. 70 students from the 4th, 5th and 6th grades (ages 8-12), three teachers and 12 parents from a public school in the province of Almeria, Spain, participated in the study. Three questionnaires were designed (for students, teachers and parents) to collect the information; they were based on theoretical models (Bisquerra & Pérez, 2007) and standardized self-report inventories in emotional competencies (Extremera & Fernández-Berrocal, 2004; Matson et al., 1983). The collected data were analyzed using descriptive statistics, a comparison between groups, and a correlation between variables. Among the main results, students reported that they did greater work in strengthening their emotional awareness, followed by emotional regulation and interpersonal relationships. There were no significant differences in emotional management and responsible decision making among students from the three academic years; however, males reported greater emotional control than females. A significant correlation between emotional competencies and responsible decision making in pre-adolescents was found. Teaching staff mentioned having done greater work in the development of students’ emotional awareness and support of their responsible decision making. Parents, in turn, seek to help their sons and daughters to be more self-reliant, in addition to working collaboratively with the school, by documenting or seeking support to contribute to education and personal development of their children.